Avrupa Merkez Bankası”nın oluşumu, para politikası, uygulama sorunları ve Türkiye”ye etkileri - Polat, Ali, 1944- (My University, 2000)
Avrupa Para Birliği kavramı, fikri anlamda 1850'li yıllara kadar uzanırken, uygulama alanında ciddi planlar ve atılımlar ancak 1950'li yıllarda gerçekleşmiştir. Siyasi ve ekonomik sebeplerle ortaya çıkan olumsuzluklar neticesi ertelenen birlik fikri 1988-1991 yılları arasındaki hızlı çalışmalar neticesinde 1992 yılının Şubat ayı'nda Maastricht Anlaşmasının imzalanması ile kesinleşmiş oldu. Bir parasal birlik oluşturmanın ekonomik faydalarının tek başına kuruluş maliyetinden daha ağır basmadığı konusundaki görüş birliği, bu projenin nihai anlamda siyasi boyutlu olduğunu göstermektedir. Parasal Birlikler ile ilgili teorik tartışma 1960'larda Mundell ile başlatılmıştır. Zaten Avrupa ülkelerinin parasal birlik konusundaki tartışmaları da dönüp dolaşıp asimetrik şoklar ve bunların üye ülkeler üzerindeki etkileri noktasında düğümlenmektedir. OPA teorisi bağlamında değerlendirildiğinde APB alanı Optimum Bir Parasal Alan değildir. Kültür ve dilleri birbirinden farklı ulusların, emekgücü olarak Avrupa içindeki dolaşımı yok denecek kadar azdır, maaş ve fiyat esnekliklerinin de oldukça düşük olduğu bu ülkelerin durumu diğer kriterler de göz önüne alındığında Optimum bir birlik oluşturmamaktadır. Avrupa ülkeleri her şeye rağmen parasal birliğe taraftar olmuşlar ve getirilen yakınlaşma kriterleri ile birlik sonrası optimizasyon şeklinde ifade edilebilecek bir strateji belirlemişlerdir. Optimal bir parasal birlik olmayan Avrupa'nın bu stratejisinin neler getireceği ise henüz belirsizdir. Bu stratejinin temel kurumu euroland ölçekli para politikasını yönetecek olan Avrupa Merkez Bankasıdır. Bu kurum iki açıdan önem arzetmektedir. Birincisi, dünyada merkez bankacılığının geldiği nokta açısından:. Geçtiğimiz son 20 yıldaki gelişmeler, ortaya çıkan yeni durum ve dünya ekonomilerinin aldığı şekillenmeler merkez bankalarının işlevlerini geniş ölçüde etkilemiştir. Özellikle finansal piyasaların büyümesi, globalleşmedeki öncülüğü ve gelişen iletişim teknolojisi bu piyasaları 60'lı, 70'li yıllardan çok daha değişik boyutlara götürdü.. Bu gelişmeler merkez bankalarının temel fonksiyonlarını da etkiledi. Temel işlevleri parasal istikrarı sağlamak ve finansal istikrarı korumak olan Merkez Bankaları, piyasa sistemlerine ağırlık veren uygulamalar artınca daha bağımsız merkez bankalarına gereksinim gösterdi. Şeffaf, açık ve bağımsız merkez bankalarının fiyat istikrarını daha iyi sağlayacakları fikri ön plana çıktı. Bir taraftan bu gelişmeler olurken, diğer taraftan da gelişen bilişim teknolojilerinin sunduğu yenilikler bazı merkez bankalarının faaliyetlerini ucuzlatırken bazılarını da pahalılaştırdı. Pahalı bir hizmet olan yeni şube açma operasyonlarına gerek kalmadı. Hatta şube kapatma ve küçülme eğilimleri başladı. Avrupa Merkez Bankası'nın kurulması ile ülke merkez bankası fonksiyonları azaldı ve kendi ülke para politikalarına yön verme özellikleri değişti. Bütün bu değişimler merkez bankalarının daha kaliteli ve az sayıda elemana ihtiyaç duymalarını da beraberinde getirdi. Bilgi işlem teknolojisindeki gelişmeler sayesinde fon transferlerinin birlik üyesi ülkeler içinde bir günde gerçekleştirilebilmesine olanak veren TARGET sistemi kuruldu. İkinci olarak da; her ne kadar Avrupa içinde ekonomik ve finansal dengeyi sağlamakla görevli olsa da, AMB, Dolar ve Yen gibi yeni bir küresel para'nın yöneticisi olacak ve ismi ve değeri olan ancak kendisini olmayan bu paranın yönetimini 11 ülke adına gerçekleştirecektir. Bu çalışma da AMB'nın fiyat istikrarlı ve parasal büyüklük hedefli yeni stratejisi açıklanmış, kullanılacak araçlar, politikalar ve bunların sağlanmasında gerekli olan şeffaflık tartışılmıştır.Bütün bunların değerlendirilmesi sonucunda, parasal birliğe geçiş ile birlikte kaybedilen ulusal merkez bankaları otoriteleri ve politika araçları (para ve döviz) nın yerini etkin ve her ülkeyi memnun edici bir aracın almadığını söyleyebiliriz. Ekonomi yönetiminin mali boyutu ve kamu kesiminin para yönetimi ile bağlantısı tamamen kesilmiştir. Para Politikası araçları ellerinden alınan ülkelere ciddi anlamda da mali kısıtlamalar getirilmiştir. Ekonomi büyürken ve gelirler artarken popüler para politikaları geliştirmek zor olmamakla birlikte, sorunlu dönemlerde AMB ne yaparsa yapsın, bazı gruplara yaranamayacaktır. Ekonomik durgunluk, finansal krizler, dış krizler gibi durumlarda uygulanacak sıkı veya gevşek para politikalarının üye ülkeler üzerine etkileri farklı olacaktır. Bu zamanlarda farklı ülkelerin AMB'dan farklı talepleri olacak ve hatta siyasi baskı haline bile dönüşebilecektir. Bu noktada, kurulan bu yeni bankanın güven sorunu olduğundan bahsedebiliriz. Piyasaların güveni sağlanmadan euro'nun beklenen etkiyi yapması sözkonusu olamayacaktır. AMB'nın Amerika'daki Federal Reserve ve Alman Merkez Bankası'na benzeyen yapısına rağmen, bu iki bankadan daha az güven telkin edici olduğunu -şimdilik- söyleyebiliriz. Bu noktada, AMB'nı tüm bu baskılardan bağımsız hareket edebilmesi için de kurumsal, finansal, personel ve fonksiyonel yönden bağımsızlığının sağlanması gerekmektedir. Siyasi baskılardan uzak bir şekilde görevini yerine getirebilmelidir. Aslında, merkez bankasının apolitik olması kendi tanımı içinde çelişiktir. Birçok ülkenin içindekinden çok daha fazla farklılığa sahip bölgeler ve çıkarlar arasında denge sağlamak gibi zor bir görevi vardır ve finansal piyasaların güvenini kazanmak için yoğun bir çaba içindedir. AMB başkanlığının siyasi boyutu ile ilgili diğer bir durum da Fransız ve Alman kanatlarının başkanın kim olacağı ile ilgili tartışmalarıdır. Birliğin son aşamasında bile Avrupa ulusları hala ulusal kimliklerinden ve çıkarlarından vazgeçememişlerdir. Bütün bu gelişmelerin Türkiye'ye olan etkisi ise birçok etkene bağlıdır. Fakat, Euro ile ilgili bütün gelişmelerden, olumlu ya da olumsuz, en başta ve yüksek oranda etkilenecek ülkelerden birisi Türkiye'dir. Dış ticaretimizin yarısı üye ülkelerl yapılırken, işçi dövizlerinin büyük bölümü,döviz tevdiat hesaplarının yaklaşık %40'ı ve Merkez bankası döviz rezervlerinin %60'ını sözkonusu ülkelerin paraları oluşturmaktadır. Yüksek oranlı mal ve hizmet ticareti yapılan ithalat ve ihracat işlemlerinde Euro'nun kullanımının (AMB'nın politikalarına ve Euro'nun değerine bağlı olarak) artmasını bekleyebiliriz. Ancak, Euro'nun Avrupa içi ticareti arttırıcı etkisi sebebiyle Türkiye'nin Avrupa'ya olan ihracatında düşüş yaşanabilir. Ayrıca, üye ülkelerin vergi oranlarındaki yakınlaşma ve fiyat düzeyindeki düşüşler, Türk mallarının hem Birlik içinde hem de üçüncü ülkelerde rekabet gücünün azalmasına sebep olabilecektir. DM ve diğer Avrupa paralarının yerini orta vadede Euro kullanımı alabilir. Reel sektörde meydana gelen değişiklikler dolaylı olarak finans ve bankacılık sektörünü de etkileyecektir.EEuro'nun kullanımı ile birlikte dış borçlanma stratejileri de etkilenecek ve euro ile dış borçlanma başlayacaktır. Türkiye gibi yıllardır yüksek enflasyondan kurtulamayan ülkeler açısından da fiyat istikrarı hedefli bir para politikası, AB'ne katılım çerçevesinde düşünüldüğünde üzerinde durulması gereken diğer bir konudur. Uluslararası piyasalardaki gelişmeler, rezerv paraların birbirine etkisi ve karşılıklı etkileşimin getirdiği kontrol edilemeyen değişkenler bir kenara bırakıldığında, yeni finansal mimari çerçevesinde Euro hakkında sözsahibi olan Avrupa Merkez Bankası'nın ve uyguladığı politikaların enine boyuna değerlendirilmesi ve bunun hem global etkileri hem de ülkemiz üzerindeki etkilerinin değerlendirilmesi gerekmektedir.

The European Monetary Union stands as one of the most important economic issues of the 1990s. For many European policy-makers, this project marks the pinnacle of the move towards European economic and political integration since the end of World War II. The success of this monetary arrangement depends upon the ability of European Union (EU)-level institutions to satisfy the monetary and fiscal policy demands of sufficient numbers of national constituents, interest groups, and multi-national corporations. The dissertation provides an analysis of the EU's one of multi-national monetary authorities which is ECB, supranational monetary authority, and its national central banks which are constituted ECBS. The first chapter provides a brief survey of Western European efforts at economic and political integration since the middle of the nineteenth century. During this period, a number of customs and monetary unions formed and subsequently disbanded. The disintegration of these unions resulted from economic circumstances that drove national governments to undertake divergent policies. After giving an historical background, the newly established structure of the ECBS and its bodies are examined in detail. The second chapter provides a theoretical overview of issues relevant to the creation and operation of currency unions drawing from the optimum currency area theory literature. Foremost among the criteria that define an optimum currency area is the suitability of a single monetary policy response to economic disturbances for the participating regions, particularly following economic disturbances. Whether or not a single monetary policy is suitable for one or more regional economies depends upon the similarity of economic disturbances and the operation of sufficient adjustment mechanisms. Adjustment mechanisms include, but are not limited to, exchange rate flexibility, factor and output market flexibility, industrial and portfolio diversification, economic openness, and fiscal policy. The institutional framework of a currency union also plays an important role in determining the success of single currency areas. The introduction of a currency union may include the transfer of monetary policy to a new central institution. This transfer implies that individual regions no longer retain authority over monetary and exchange rate policy. Fiscal policy may also be subject to constraints because of participation in a currency union. The third chapter provides information about the new monetary policy and its instruments. By giving a special importance on price stability which is defined clearly, the new monetary policy will be responsible for maintaining price stability all over the monetary area. In order to reach price stability, which is ultimate target there may be, different monetary strategies as well as different intermediate targets. A suitable mixture of these strategies and intermediate targets will be formed to achieve price stability. The fourth chapter examines the implications of EMU for monetary and fiscal policy and institutions. Participating in the EMU implies that countries surrender monetary and exchange rate policy to the ECB. If needed changes are not supplied, it is possible to experience some economic shocks. The chapter also discusses economic shocks in the context of EMU. A number of studies attempt to empirically determine whether regions of the EU are subject to asymmetric shocks. ECB will be responsible for practicing Monetary Policy in the euro area. This new monetary and political transformation makes the ECB one of the most important authorities in the area. After the transformation, Europe will be another economic zone like America or Asia. In turns of relation of the currencies such as US Dollar, Yen and Euro, the policies, which will be applied by the ECB, will have a special importance not only in the Europe but also in the World. Historical Background The original European Economic Community hardly mentioned the concept of money. It was negotiated in the mid-1950s when the devastating impact of he Second World War on the Member States was gradually being overcome: the rebuilding European economies were not yet ripe for the immediate opening of borders for products from other Member States. The idea of establishing an economic and monetary union among its members, although not contained in the EEC Treaty, is almost as old as the European Economic Community itself. In the late 1950s, Jean Monnet, who had fathered the idea of European integration through common institutions, proposed a European Reserve Fund. In the early 1960s, the Commission argued that a customs union was inevitably to lead to economic and monetary union. In 1964, the Council created a body of central bankers to discuss the coordination of monetary policies. 1n 1968, a year which saw the beginning of the demise of the Bretton Woods monetary order, the Commission was actively promoting the idea of EMU. The monetary disturbances, which were, from the early 1970s onwards, to lead to general floating of the major currencies, had divergent influences on the currencies of the Member States. At a meeting in the Hague, the Heads of State and Government decided to proceed with EMU. A study group headed by Pierre Werner, Luxembourg's Premier and Finance Minister was entrusted with the task of reporting on the establishment of EMU. Its report mapped out a road to EMU in three stages. Full EMU was to be achieved by 1 January 1981. The good intentions did not materialize, however, as the efforts watered down when the oil shock of 1973 and the subsequent severe economic setbacks led to national instead of Community responses. High inflation, rising unemployment and major restructuring characterized the 1970s, with economic policy responses at Community level playing only a secondary role. A Council Decision of 22 March 1971 initiated a strengthening of the cooperation between the central banks. Pursuant to paragraph 7 of the EMU Resolution of 22 March 1971, the central banks were invited to arrange for the exchange rate fluctuations between the Community currencies to be kept within margins narrower than those, which resulted from the margins which were maintained in respect of the US dollar. As it is called snake the General elements of EMS are; · An exchange rate mechanism (ERM) between the participating currencies; · The creation of ECUs against the deposit of foreign reserves of all Member States; · Mechanisms to provide credit to the participating central banks in order to maintain the central rates agreed, and coordination of the economic and monetary policies to underpin the currency arrangement. The Delors Committee report defined economic and monetary union as the Werner Report of 1970 had done before it. EMU would imply complete freedom of movement for persons, goods, services and capital, as well as irrevocably fixed exchange rates between national currencies and, finally, a single currency. The 1989 Report lays emphasis on the necessity of embedding national, and regional, economic policy decisions in a Community framework. Thus, it can be said that EMU as seen by the Delors Committee consists of three elements: · The completion of the internal market, · The establishment of a fair measure of coordination of the economic policies of the Member States (economic union), and · The fixing of the exchange rates between the currencies and the subsequent introduction of a single currency (monetary union). The Maastricht Treaty on European Union, agreed during the December 1991 European Council meeting in Maastricht in the Netherlands, was signed, in the same city, by the Ministers of Foreign Affairs and of Finance of the Twelve on 7 February 1992. The Delors Committee's ideas on three successive steps to reach full EMU were likewise followed. Stage 1 started before the amendments to the Treaty of Rome were discussed, let alone adopted. Stage 2 started on 1 January 1994, and the third and final stage will commence not later than 1 January 1999. Although there were some reflections of the Maastricht in different stages, on the monetary side, the innovation of the second stage concerns the establishment of a new body, the European Monetary Institute. It is entrusted with the dual tasks of coordinating monetary policy, which firmly remains a matter for the Member States and of preparing the changeover to the final stage when the single currency and its monetary policy will be managed by the EMI's successor, the European Central Bank. The Delors Committee Report had proposed that the ESCB be established as of Stage 2 of EMU. Thus, experience with the formulation and operation of a common monetary policy could be gained until, at the beginning of Stage 3, it would assume all responsibilities. Upon its establishment, ECB will take over the tasks of the EMI, i.e., the coordination of monetary policies and the preparations for Stage 3 of EMU. Only on the first day of this stage will the ECB assume its full powers. Thus, during this brief interval, the ECB will perform the functions which, for the larger part of Stage 2, will have been exercised by a separate institution. The EMI is a separate legal person governed by a Council which brings together the Governors of the NCBs and an outside President. The appointment of an outside president to chair the management of the EMI, a responsibility that he shares with NCM Governors, is an institutional novelty compared with the EMI's predecessor. The final stage of EMU will imply the irrevocable locking of the exchange rates of the participating currencies. Pursuant to Article 109 J and EC Treaty, it will start on 1 January 999 at the latest, the earliest possible date for commencement of Stage 3 being 1 January 1997. The transition to Stage 3 also implies the application of a few stricter provisions in the area of economic union. Only States qualifying under the strict economic admission criteria will be admitted while, in addition, the relevant legislation must have been found to be in conformity with the provisions on EMU, notably on the independence of the central banks. The ESCB or the System as it is also referred to, is composed of the ECB and the NCBs. It consists of sixteen central banks. The NCBs are legal entities formed under the laws of their respective States. The ECB is a legal person, formed under Community law. The system itself does not have legal personality. It is the common name for the joint operation of sixteen legal entities, to with the fifteen National Central Banks and the ECB. The System has a clear line of command: it is governed by the decision-making bodies of the ECB. The ECB is to ensure that the tasks of the System are carried out, whether through its own activities or through the NCBs. Therefore, the NCBs are subject to instructions of the ECB. The governing bodies of the ECB are the Governing Council and the Executive Board. The Governing Council consists of the Executive Board plus the Governors of the NCBs. This composition of the highest governing body of the ECB ensures that the federal element (the Executive Board) and the regional input (the NCB Governors) are brought together in the decision-making procedure. The Governing Council shall formulate the monetary policy of the Community. This encompasses taking the decisions on monetary objectives, on key interest rates and on the supply of reserves in the ESCB'. The Governing Council is also to adopt the necessary guidelines for the implementation of monetary policy. The Governing Council is the supreme decision-making body on all matters relating to the tasks of the System. The Treaty reserves for it, in particular, 'all strategic monetary policy decisions.' Furthermore, it is up to the Governing Council to decide on issues pertaining to the ESCB's financial matters. The Executive Board consists of the President and Vice-President of the ECB, and four other members. They have appointed for non-renewable eight-year terms 'by common accord' of the Governments of the Member States. The Executive Board is to implement monetary policy, in accordance with the guidelines and decisions of the Governing Council. As long as there are States with a derogation, a General Council will be functioning as the third governing body of the ESCB. It consists of the President and Vice-President of the ECB and the Governors of all NCBs, with the other Executive Board members participating without a right to vote. The Theoretical Background: Optimum Currency Areas The traditional approach to determining whether a country should participate in a common currency or should instead maintain its separate currency tried to identify crucial economic characteristics that would sere as criteria for determining the optimal domain of a currency area. Optimality requires that the existence of a common currency should not reduce the ability of member states to adjust to shocks or increase their vulnerability to such shocks. The leading contributors to this optimum currency area debate have emphasized different attributes whose existence in the area would enable the effects of country specific shocks on output and employment to be overcome, when movements in intra-block exchange rates are no longer available for that purpose. The traditional model of monetary integration started with the theory of optimum currency areas. This theory was a purely academic exercise during the 1960s. The most important contributor to this debate was Mundell (1961), who identified factor mobility as the strategic attribute of an optimum currency area. According to him, when factors move freely within the area, adjustments to real disturbances can take place without the need for large and damaging price and income changes among its constituents members. McKinnon emphasized instead the importance of a high degree of openness of the individual economies, which is crucial for determining the extend to which the prices of domestic outputs must remain in line with foreign prices. Kenen stressed the significance of a high degree of product and exports diversification, the lower the effects of real disturbances. Coordination of economic policies can be a criterion for economic and monetary union. Economic policies, which are not coordinated among countries, may be a major reason for the disturbance in the equilibrium of the balance of payments. Coordination of economic and monetary policies from a supranational center requires political will on the part of the participating countries. One criterion for monetary integration may be a similar level of inflation among the potential member countries. Diverging ratios of employment to inflation among these countries will cause problems. An optimum currency area may be defined as a region in which no part insists on creating money and having a monetary policy of its own. A monetary union, which imposes minimum costs on the participating countries may be, called an optimum currency area. An OPA may be alternatively defined as area in which the benefits of integration outweigh the costs. An optimum currency area aims at identifying a group of countries within which it is optimal to have fixed exchange rates while, at the same time, keeping certain flexibility in the exchange rate with the third countries. Very small currency conversion costs and openness is likely to make an EU an OPA, while the high levels of government spending will make the EU less likely so. An OPA may also be defined as one that attains the macroeconomic objectives of internal balance. The shortcomings of the traditional single-criterion and optimum currency model of international monetary integration may be overcome by the new theory of monetary integration that relies on the cost-benefit model. Monetary integration brings a number of benefits. These comprise a release of the exchange problems within the group of countries in the arrangement, an increase in the influence in monetary affairs and an increase in monetary stability. The costs, which may be brought by a country's participation in monetary integration, can be various. Some of them are the losses of a country's right to change independently its rate of exchange, its ratio between inflation and employment, its ability to control its regional development policy and its seignorage. The fundamental economic case for imposing monetary integration upon product and factor market integration is that it will make the integration of these markets more effective, with beneficial effects on resource costs, economic efficiency and growth. The benefits of monetary integration are numerous. The most important benefit of monetary integration is that it improves the integration of markets of goods, services and factors. Exchange rate risk for trade flows among the integrated countries is eliminated, transaction and hedging costs are reduced, so investors can make their decisions with a high degree of long-tem confidence. The elimination of exchange rate uncertainty reduces risk and causes a decline in the risk-adjusted cost of capital. One other benefit of monetary integration can be described as the pooling of national reserves of foreign currencies. This can be advantageous for the member countries of an EMU. By internalizing their foreign trade, these countries reduce their demand for foreign currency reserves. These reserves may not be necessary for trade within the group, but they may still be needed for trade with third countries. A third important benefit is brought by the high degree of integration of financial markets that would necessarily implied in a situation of monetary integration. A fourth potential source of benefit results from the savings to be expected from the elimination of the direct transaction costs involved in converting one currency into another. The net effect of monetary integration may not be easily and directly quantified. On the other hand, the costs of monetary integration in the form of an increase in prices or unemployment are relatively easily identifiable and they are generally in short-term. The first and most visible inconvenience of a monetary union is the loss of national sovereignty. The creation of a supranational body to conduct monetary policy in an EMU may be perceived as a significant loss of the participating countries' national sovereignty. The most sensitive issue may be the loss of the right to change independently the rate of exchange. The loss occurs fully against the currencies of partner countries and partially against other countries. However, the pooling of monetary policies of the member countries can be more favorable for their monetary policy in comparison to the situation prior to integration. The second cost of monetary integration is that it prevents countries to use as an economic policy alternative among unconstrained choices between unemployment and inflation. It was argued that floating exchange rates permit unconstrained choices between unemployment and inflation in a country. On those grounds, countries may seem to be free to pursue their own stabilization policies. An EMU constrains the independent national choice of the rates of inflation, unemployment and interest rate. The third problem of a monetary integration is that the institution of a monetary union that would require the acceptance of a common rate of inflation would not necessarily indicate the balanced growth of the member countries in the sense of equal real wage growth. Productivity growth rates may differ between the member countries. The fourth difficulty of monetary integration is the issue of the differences between countries in terms of their exposure to demand shocks ad supply side disturbances such as raw material shocks or productivity changes. There may be significant costs for a country that would be attached to the establishment of a common currency in a complete monetary union. There can be the adjustment costs of the transition to monetary integration involved in the achievement of a common rate of inflation and furthermore, the adjustment costs associated with later shocks and disturbances. The fifth cost of a monetary union can be described as the inflow of capital into the wealthy region or country. The fifth problem can be the loss of seignorage in an EMU. Instead of selling debt, a government may print money and raise revenue in order to cover its budget deficit. The government is taxing the holders of cash held by the public and the commercial banks' low-interest bearing deposits held at the central bank. Monetary Policy, Instruments and Price Stability Target of ECB Monetary policy in the euro currency area will be formulated and implemented by the ESCB, comprising the ECB and NCBs. The ESCB has been mandated by the Maastricht Treaty to ensure price stability within the euro area. This narrowly defined objective is protected from political interference by statutes based on an international treaty which only member states acting collectively can alter. This confers the ESCB with a high level of independence in the pursuit of its objective However, the Treaty also states that without prejudice to the objective of price stability, it shall support the general economic policies in the Community Given that the newly formed ESCB will have no track record in the fulfillment of its price stability objective, it is imperative that credibility is established at the start of EMU. The ESCB will have to choose the monetary policy strategy that will best deliver the credibility. A suitable strategy for monetary policy should satisfy a number of criteria. The strategy should be effective in meeting the objective of price stability, the process of setting targets and decision making should be transparent to the public; the formulation and communication of the targets should be such as to hold the monetary authority accountable to the public for its action; it should have a medium-term focus to lock-in inflationary expectations, while retaining some discretion in responding to short-run deviations from the target; as far as possible there should be continuity with the experiences of the strategies used by the participating NCBs and finally it should be consistent with the independence of the ESCB. There are different strategies and each strategy has an ultimate target, which is price stability. However, in order to pursue this objective an intermediate target and/ or indicator is utilized. Intermediate targets for monetary policy are required due to the uncertainty that arises between the use of monetary policy instruments and the ensuing effectiveness in achieving the objective of price stability. The EMI considered five possible strategies for monetary policy within EMU. These strategies were interest rate targeting, nominal income targeting, exchange rate targeting, monetary aggregate targeting and direct inflation targeting. In practice, considerable overlap exists between the ESCB's candidate strategies of monetary aggregate and inflation targeting. Both pursue the same objective of price stability. The operational framework consists of a set of instruments; the ESCB will conduct open market operations, it will offer standing facilities and it may require credit institutions to hold minimum reserves on account with the ESCB. Open Market Operations: Open Market Operations will play an important role in the monetary policy of the ESCB for the purpose of steering interest rates, managing the liquidity situation in the market and signaling the stance of monetary policy. Standing facilities aim to provide and absorb overnight liquidity, signal the general stance of monetary policy and bound overnight market interest rates. Two standing facilities, which will be administered in a decentralized manner by the national central banks, will be available to eligible counterparts on their own initiative. Minimum Reserves: Preparatory work has been carried out with a view to enabling the ESCB to impose minimum reserves as from the start of Stage Three. It will be up to the Governing Council of the ECB to decide whether minimum reserves will actually be applied. Any minimum reserves system would be intended to pursue the aims of stabilizing money market interest rates, creating a structural liquidity shortage and possibly contributing to the control of monetary expansion. The reserve requirement of each institution would be determined in relation to elements of its balance sheet. In order to pursue the aim of stabilizing interest rates, the ESCB's minimum reserves system would enable institutions to make use of averaging provisions. This implies that compliance with the reserve requirement would be determined on the basis of he institutions' average daily reserve holdings over a one-month maintenance period. In the context of this strategy the ECB has provided a quantitative definition of price stability. Price stability is defined as a year-on-year increase in the harmonized index of consumer prices (HICP) of below 2% for the euro area as a whole. Price stability is to be maintained in the medium term. The strategy consists of two pillars. The first pillar is a prominent role for money. The reference value for the growth of a broad monetary aggregate, M3, of 4.5% on an annual basis. In order to evaluate the quantitative definition of price stability a new index is created which is HICPs. (Harmonized indices of consumer prices). The first set of HICPs was published in March 1997, with historical series dating back to January 1995. After euro a new interest rate, which is Euribor, Euro Interbank Offered Rate, is used as the benchmark rate of the large euro money market. It is sponsored by the European Banking Federation which represents 2800 bank in the fifteen Member States of the European Union. Euro Libor, Euro London interbank offered rate, is used as rate of euro in the UK's markets. British Banking Association is started to use this rate after 1 January 1999. One another type of rate is Eonia, Euro Overnight Index Average, is an effective overnight rate computed as a weighted average of all overnight unsecured lending transactions in the interbank market, initiated within the euro area by the contributing panel banks. Transparency and Accountability Accountability for policies is the logical complement to independence in a democratic society. The Maastricht Treaty includes a number of provisions in this respect. First, there is the mandate to pursue price stability. This provides a qualitative measure against which the ECB's performance can be measured. The ECB has to publish an annual report in which, inter alia the monetary policy of the previous and current year is discussed. The ECB has to report on its activities at least quarterly. Economic hetorogeneities and limited adjustment mechanisms shed strong doubt on the suitability of a common monetary policy. Fiscal limits on national debt constitute a further constraint on regional adjustment policy. Economic shocks may lead to divergent monetary and fiscal policy preferences among EU constituents. In response, domestic demanders of policy call on their national representatives to promote and secure policy favorable to their interests within the decision framework of the EU. Target In 1998 intensive work continued on the implementation of the TARGET (Trans European Automated Real-time Gross settlement Express Transfer) system. With the operation of the TARGET payment system integrating the inter-bank markets in the monetary system, the financial markets will become deeper and more liquid. The more competitive environment will reduce the cost of financial intermediation and stimulate the investment activities in the financial markets. The relation of Monetary and Fiscal Policy in EMU The inclusion of restrictions on fiscal policy in a treaty which, after all, aims at monetary union, is a source of considerable debate. Before the Maastricht Treaty, most academic analyses emphasized that national fiscal policy would have to become more active to compensate for the loss of the exchange rate instrument. The opposite approach, that monetary union requires fiscal policy restraint, is grounded in the view that excessive budget deficits may lead to eventual monetization of he debt. Monetary authorities were clearly concerned by high debts in some countries, especially in Italy, whose public debt represent some 18 percent of Europe's GDP. They feared that an explicit or implicit lender-of-last resort function might force the ECB to step in and indirectly monazite a country's public debt if banks faced a financial crisis in the wake of a default. This concern is reflected in the budgetary criteria for EMU membership and in the excessive deficit procedures designed to enforce fiscal rectitude once in the monetary union. While it is difficult to disagree with the view that fiscal policy ought not to jeopardize monetary and fiscal stability, how to provide the incentives for appropriate fiscal policy is open to debate. The debate implicitly revolves around one's view of the ability of fiscal policy to play a macroeconomic stabilizing role. It also hinges on the ability to define at the time a deficit is enacted that it is excessive. In principle, the proper answer must be in terms of sustainability since unsustainable debt buildup will eventually have to be reversed (by definition.) Fiscal policy sustainability is also associated with stationarity of the debt, usually defined as a stable debt/ GDP ratio. The Maastricht approach, relying o arbitrary quantitative limits, is quite unsophisticated. The 3 percent annual debt/ GDP rule corresponds to what is called the golden role in Germany: governments may only borrow to pay for investment spending, and in turns out that governments usually dedicate about 3 percent of GDP to such spending. Even if one ignores doubts about the 3 percent estimate itself, the rule is naive at best; it ignores socially productive spending like education which is classified as consumption, while it may include ill-designed investment spending. The 60 percent debt/ GDP was chosen because it was the average of EU countries when the Maastricht Treaty was being negotiated, with not even the pretense of any justification. Independence In EMU, Independence from political authorities will allow the System to define a monetary policy aimed at the statutory objective of price stability. Independence also requires the System to possess the powers necessary to implement monetary policy decisions. Central Bank independence is essential for the credibility of the move to Monetary Union. The EMI has established a list of features of central bank independence, distinguishing between features of an institutional, personal and financial nature. Institutional independence is a feature of central bank independence, which is expressly referred to in Article 107 of the Treaty. This Article prohibit the ECB, the NCBs and members of their decision making bodies from seeking or taking g instructions from Community institutions or bodies, from any government of a Member State or from any other body. It also prohibit Community institutions and bodies and the governments of the Member States from seeking to influence the members of the decision-making bodies of the NCBs whose decisions may have an impact on the fulfillment by the NCBs of their ESCB-related tasks. Personal independence is provided with the Article is that a minimum term of office for a governor is five years. It also gives protection against the arbitrary dismissal of governors. Financial independence is also a requirement for an independent central bank. The finances of an independent central bank do not come under the budget authority of Parliament nor are they subject to approval by the Mister of Finance. His influence on the distribution of the central bank's profit is circumscribed by law in a transparent way. The authority of state organs to verify the accounts of the central bank may not lead to an influence on its policies. Thus, the function of a State audit body is limited to the scrutiny of the central bank's efficiency. The effects of Euro on Turkey The Association Agreement of Ankara of 1963 recognized the objective of a gradual establishment of a Customs Union between turkey and the EU, with a view to the possible accession of Turkey into the EU at a later stage. Following several delays, the agreement implementing the final phase of the Customs Union was signed on December 22, 1995 and entered into force on December 31, 1995. Turkey as a candidate country should be in the position to participate in EMU as non-participants in the euro area, but still need to make substantial efforts towards macroeconomic stabilization. On the other hand, Turkey will undoubtedly be affected from the EMU which most likely will produce various outcomes for the country's structural change observed in its markets as well as for a new design of its economic policies. The EMU and the introduction of the euro is very important for Turkey considering its close relation ship with the EU. The EU area is Turkey's largest partner. In 1998, 50 percent of exports and 52 percent of imports were to and from EU countries, reflecting the increase in trade relations since the Customs Union Agreement came into force at the end of 1995. The ability of the candidate countries to adhere to the aims of EMU was explicitly mentioned by the Copenhagen European Council as one of the criteria for EU membership. Policy makers in these countries interpreted this as meaning that their countries should meet the Maastricht criteria on inflation, government deficit, public debt, long-term interest rates and exchange rate stability as a precondition for joining the EU. However, the Maastricht convergence criteria are not accession criteria. The Copenhagen criteria refer to ability of applicant countries to adhere to the aims of EMU rather than the ability to actually join the euro area. As Turkey is a member of the Customs union, it well be affected in medium and long term positively by the economic growth and welfare of the union. Moreover the introduction of euro will enhance the competition and Turkey can enjoy the external benefits of the enhanced competition. Though in this period Turkey must take necessary precautions and implements structural reforms to manage with the inflation and to stabilize the value of its currency against euro. The extent of he effects of the last stage through the economic integration, the introduction of he common currency on the Turkish financial sector -the capital and money markets and financial institution- are still indeterminate. Beside the precautions that the European financial institution are taking in the changeover process and their adjustment strategies are worthwhile to analyze. Especially the wave of mergers in the banking sector signals a similar development in the Turkish banking sector and it will be very useful. The decrease of the exchange rate risk and the further decrease of the interest rates with the introduction of euro will reduce the transaction costs and will have positive impact on the relations of the Turkish financial sector with the union. The banks are already reserving the adequate information technology resources in anticipation of the changeover processes however a long and costly preparation period consisting of evaluating and adapting the information systems is necessary in order to be effective and operational both during and after the transition period to the euro. In fact the Turkish Central Bank started to carry out the adjustment of the national regulation system, Foreign Currency Accounts, with letter of guaranty the acceptance of the Turkish banking sector to the TARGET payment system. The start of economic and monetary union will result in a tendency of the interest rates and the profitability (due to the increased competition) to decrease. Turkish financial sector where the risk and profitability are at high levels this will most probably stimulate the investments. There are different aspects of the relation between Turkey and EU. For example in EU, all member states should ensure that their national legislation including the central bank statutes is compatible with the Treaty and the Statutes of the ESCB: This implies that their central bank governors should be elected for terms of no less than five years and should only be dismissed under circumstances of serious misconduct or inability to perform their duties, that their central banks should not take any instructions from the government and that they should have as primary objective the maintenance of price stability. The Central Bank of Turkey Board consists of Governor and 6 other members. The governor is appointed by the government for 5 years upon Board proposal. Other members are appointed for 3 years by the CB's General Assembly of Shareholders. All members can be reappointed. Within this context, it should be said that although the Turkish CB enjoys a degree of factual independence, its statutes still need to be aligned to assure the full legal independence of the monetary authorities. The Maastricht Treaty requires all countries to renounce any from of direct central bank financing of government deficits. Turkey has flexible rules on central bank financing. She allows advances from the central bank and leaves freedom to the central bank and government to agree on the interest rate applied. As a result, although Turkey had taken a number of steps to reduce the de facto access of their treasuries to central bank financing, she still need to reform substantially her rules on the matter to comply with EU standards. Liberalization of Capital Flows is also important in EU: Turkey undertook a substantial liberalization of its capital account during the 1980s and first half of the 1990s, partly reflecting its obligations as a member of the OECD. The prospect of EU membership increases pressure on non-EU candidate countries to continue to make progress towards developing a healthy, efficient, and market-oriented financial sector. However, Turkish financial sector still suffers from a number of problems. The Impact of the euro on Turkey can be classified as systemic which are stability of euro and portfolio reallocation and effects on the Balance of payments which has an effect on trade of goods and services. EMU is likely to have o positive effect on European growth. This favorable effect is expected to come from a combination of developments, such as price and exchange rate stability and fiscal consolidation policies. The launch of euro is expected to enhance the benefits brought about the completion of the single integrated European market. The degree of the euro to influence the Turkish economy will be related to its future trend vis-à-vis the USD, JPY and naturally, the TL. The appreciation of the euro in foreign markets will cause an increase in Turkish exports ad a fall in imports. On the other hand, in order to have a more accurate view about the net impact on the exports and imports, one must look at the movement of other exchange rates such as the USD and JPY vis-à-vis the euro, which Turkey uses, in its foreign trade. Within the context, Turkey is expected to gain both enhanced opportunities and stronger competition in EU markets and will take advantage of the lower borrowing costs stemming from more competitive European financial markets. A positive output effect in the order of 0.3% of GDP is projected for the developing countries taken as a group after 10years. With Europe being the major market destination of Turkish exports, the growth effect in Turkey is likely to exceed that for developing countries. According to another IMF study, 1 percent higher GDP in the EMU countries positively influence the rate of output in Turkey by 0.1 percent and the rate of exports by 0.8 percent. Econometric studies made in Turkey indicate that Turkish exports towards the OECD countries are sensitive to the revenue increases in these countries. Another analysis shows that the positive impact of the euro on the economic growth of the EMU countries will accelerate the rate of increase of the Turkish exports by 200. In this light, the expected economic growth and the trade creation effect resulting from that economic growth would be beneficial for Turkey in the case of the realization of some factors. These are the followings: · Macroeconomic and political stability in Turkey · Strategies, which Turkish firms, would apply to increase their competitiveness · Policies implemented in the euro area and the effect and extension of these polices · Capacity of the euro to become a payment/ vehicle and intervention currency in international markets. · Stability of the euro against the major international currencies such as the USD and JPY · Demand elasticity of the euro-zone countries against the Turkish export products. · Foreign trade elasticity of the euro-zone countries' economic growth. Recapitulating the matter, it can be said that whether it has positive or negative effects, this transformation has results on Turkey. Turkey should be aware of that and doing so, he should take the necessary steps as early as possible.
Keywords: Avrupa Merkez Bankası; Bankalar ve Bankacılık, Merkez-Avrupa